Estrutura de assembléias de peixes em uma área de exploração petrolífera na Amazônia (Bacia do Rio Urucu, Amazonas, Brasil). - Costa, Igor David da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2009)
The objective of this study was to characterize fish assemblages of the Urucu River in areas of close proximity to oil and natural gas exploration, and to investigate whether there was any impact on the assemblages associated with these activities. The collections were made in an area upstream of the ports, for control (PCONT) (4 ° 51 '20.7''S - 65 º 20' 53.2''W), also held collections downstream (500 meters ) port Urucu (PJU) (4 ° 50 '59.3''S - 65 º 20' 37.4''W) (Figure 3). The collections were also held in front of the port Evandro 2 (PPE2) (4 ° 45 '47.9''S - 65 º 02' 46.6''W), 90 km equidistant urucu the port and the amount (PME2) (4 º 45 '42''S - 65 º 20' 37.4''W) and downstream (PJE2) of the same port (4 ° 45 '26.4''S - 65 º 02' 38.7''W), also captures were performed in front of the port Evandro 1 (PPE1) (4 ° 45 '18.1''S - 65 º 02' 40.9''W) and downstream of that point (PJE1) (4 ° 45 '02.2'' S - 65 º 02 '42.6''W) is located on all these points Urucu river in the city of Coari, Amazonas, Brazil. In total, 923 fish specimens from 7 orders, 23 families and 82 species were collected, with a total biomass of 166.82 kg. Characiformes were the predominant group followed by Siluriformes, while Clupeiformes, Osteoglossiformes, Perciformes, Beloniformes and Pleuronectiformes together amounted to less than 10% of the total capture. The Characidae family (30%), and sub-families Serrasalminae (15%) and Osteoglossidae (13%) were the most abundant during the low water period, while the Characidae (42%) and Callichthydae (16%) families, and sub-families Serrasalmidade (14%) and Pristigateridae (11%) were the most abundant during high water. The most abundant families per collection point during high water were: Characidae at PCONT (43%), PJU (48%), PME2 (34%) and PJE1 (52%) e PJE1 (51%), Osteoglossidae at PPE2 (42%) and Hemiodontidae at PJE2 (24%). During low water the most abundant families were: Characidae at PPE2 (54%), PME2 (38%), PCONT (45%), PJU (37%) and PJE2 (24%), and Callichthyidae at PJE1 (40%). The piranha species Serrasalmus rhombeus presented the highest abundance (11%) and occorrence frequency (91%), followed by Bryconops alburnoides, Dianema urostriatum and Osteoglossum bicirrhosum. Fish abundance, CPUE, biomass, species richness, Shannon diversity index, uniformity and dominance all varied between the two hydrological periods. The high water period presented 489 specimens and the dry period 439. The largest ratio of abundance/biomass was encountered at PJE1 during the high water period (n=122/15.17 g) and the smallest at Pcontrol during low water (n=32/5.95 g). CPUE based on abundance was largest during high water (0.33) and lowest during low water (0.30). PJE1 presented the highest CPUE (0.50; high water) and PCONT the lowest (0.13; low water). The highest and lowest species richness, respectively, were encountered at PJE1 during high water (35) and at Pcontrol during low water (12). The highest (4.22) and lowest (0.80) levels of diversity, calculated by the Shannon Index, were encountered at PJU during high and low water, respectively. PJU and PJE1 presented the highest values of uniformity during low water (J'=0.90), while PJU presented a much lower value at high water (J'=0.20). The largest dominance was encountered at PPE2 during high water (0.19) and the lowest at PJU during low water (0.07). The dominant species per collection point were: Dianema urostriatum at PJE1 and PJE2, Bryconops alburnoides at PPE2, Chalceus erythrurus at PJU and Serrasalmus rhombeus at Pcontrol and PME2. In terms of petroleum contamination, sampling point PCONT was classified as Stage I, which is associated with some physiological stress for aquatic fauna coping with moderate levels of pollution. Based on ABC curves and numerical indexes, it’s not possible to clearly determine if points downstream from PCONT were being impacted from petroleum exploration in the region. However, for PJU, which was classified as very polluted and is located immediately downstream from Port Urucu, this argument makes sense. Significant levels of aliphatic hydrocarbons indicate that contamination from sources petrogênicas were not detected by chemical analysis of water taken. The highest concentrations of n-alcanes (n-C29 during low water and n-C31 during high water) were found to be derivatives of vegetable matter combustion. From all of the environmental variables analyzed, stream width separated the collection points into two groups, with one formed by PCONT, for both hydrological periods, and the other made up of the rest of the collection points. An increase in width going downstream is consistent with the River Continuum Concept, which explains how diverse changes in hydrology occur from the headwaters to the mouth of a stream or river. Width, depth, temperature and alyphatic hydrocarbon concentrations were the principal structured variables of the studied assemblages.
Keywords: Ictiofauna; Assembleia de peixes; Rio Urucu